Enhancing CO2 Electroreduction Precision to Ethylene and Ethanol: The Role of Additional Boron Catalytic Sites in Cu‐Based Tandem Catalysts - Fuqing Yu; Minxing Shu; Guangyao Zhang; Qiming Yu; Hongming Wang (Advanced Science)
Abstract The electrocatalytic conversion of carbon dioxide (CO2) into valuable multicarbon (C2+) compounds offers a promising approach to mitigate CO2 emissions and harness renewable energy. However, achieving precise selectivity for specific C2+ products, such as ethylene and ethanol, remains a formidable challenge. This study shows that incorporating elemental boron (B) into copper (Cu) catalysts provides additional adsorption sites for *CO intermediates, enhancing the selectivity of desirable C2+ products. Additionally, using a nickel single‐atom catalyst (Ni‐SAC) as a *CO source increases local *CO concentration and reduces the hydrogen evolution reaction. In situ experiments and density functional theory (DFT) calculations reveal that surface‐bound boron units adsorb and convert *CO more efficiently, promoting ethylene production, while boron within the bulk phase of copper influences charge transfer, facilitating ethanol generation. In a neutral electrolyte, the bias current density for ethylene production using the B‐O‐Cu2@Ni‐SAC0.05 hybrid catalyst exceeded 300 mA cm−2, and that for ethanol production with B‐O‐Cu5@Ni‐SAC0.2 surpassed 250 mA cm−2. This study underscores that elemental doping in Cu‐based catalysts not only alters charge and crystalline phase arrangements at Cu sites but also provides additional reduction sites for coupling reactions, enabling the efficient synthesis of distinct C2+ products.